Treatment With a Three-Drug Regimen for Pulmonary Tuberculosis Based on Rapid Molecular Detection of Isoniazid Resistance: A Noninferiority Randomized Trial (FAST-TB). (25th July 2022) - De Castro, N; Mechaï, F; Bachelet, D; Canestri, A; Joly, V; Vandenhende, M; Boutoille, D; Kerjouan, M; Veziris, N; Molina, J M; Grall, N; Tattevin, P; et al.
Abstract: Background: The rationale behind the use of ethambutol in the standard tuberculosis treatment is to prevent the emergence of resistance to rifampicin in case of primary resistance to isoniazid. We evaluated whether early detection of isoniazid resistance using molecular testing allows the use an ethambutol-free regimen. Methods: FAST-TB, a phase 4, French, multicenter, open-label, non-inferiority trial, compared 2 strategies: (1) polymerase chain reaction (PCR)-based detection of isoniazid and rifampicin resistance at baseline using Genotype MTBDR plus version 2.0 followed by ethambutol discontinuation if no resistance was detected (PCR arm) and (2) a standard 4-drug combination, pending phenotypic drug-susceptibility results (C arm). Adult patients with smear-positive pulmonary tuberculosis were enrolled. The primary endpoint was the proportion of patients with treatment success defined as bacteriological or clinical cure at the end of treatment. A non-inferiority margin of 10% was used. Results: Two hundred three patients were randomized, 104 in the PCR arm and 99 in the C arm: 26.6% were female, median age was 37 (interquartile range, 28–51) years, 72.4% were born in Africa, and 5.4% were infected with human immunodeficiency virus. Chest x-ray showed cavities in 64.5% of the cases. Overall, 169 patients met criteria of treatment success: 87 of 104 (83.7%) in the PCR arm and 82 of 99 (82.8%) in the C arm with a difference of +0.8% (90% confidence interval, −7.9 to 9.6), meeting the noninferiority criteria in the intention-to-treat population ( P  = .02). Conclusions: In a setting with low prevalence of primary isoniazid resistance, a 3-drug combination with isoniazid, rifampicin, and pyrazinamide, based on rapid detection of isoniazid resistance using molecular testing, was noninferior to starting the recommended 4-drug regimen. Abstract : The FAST-TB trial showed that after ruling out isoniazid resistance using a nucleic acid amplification test, a 3-drug combination of isoniazid, rifampicin, and pyrazinamide was noninferior to the standard 4-drug regimen with ethambutol with regards to tuberculosis treatment success.